ANALISIS PENGGUNAAN MEDIA PEMBELAJARAN PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 1 GEDANGAN SIDOARJO - NURUL HIDAYATI (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
This study purpose to determine the learning media for teacher in SMA Negeri 1 Gedangan Sidoarjo and the reasons teachers choose the learning media, determine the feasibility of learning media, and study the response of students to the learning media used. This study is a descriptive research with quantitative approach. The results showed that the learning media used in SMA Negeri 1 Gedangan Sidoarjo is